Plantas espontâneas em sistemas de produção agroecológico, composição bromatológica, produtividade de milho e silagem de milho planta inteira - Martinez , Alexandra da Silva (2020)
The objectives of this study were carry the phytosociological survey, evaluate the frequency, abundance, density and plant importance value index in the agroecological corn crop cultivated under different crop rotation systems with cover crops in the spring/summer (first crop) and in succession in the fall/winter (second crop); evaluate the bromatological corn composition and whole plant silage in first and second crop; evaluate the corn yield, bean in succession and straw production in the different crop rotation systems. The experiment was conducted in a farm from Missal – PR, managed in agroecological system since 2009. The experimental design was of randomized blocks, with five replications. The treatments consisted of four different crop rotation systems: corn/corn/fallow/bean; corn + guandu bean/corn/oats/bean; corn + showy rattlebox/corn/forage raddish/bean and corn + jack bean/corn/vetch/bean. In the sprin/summer of 2017 the corn was consorted with the cover crops; in the fall/winter in monoculture over the straw from these crops. After the harvest of the corn second crop the cover plants were sown: forage radish, vetch and oats. In September 2018, bean were sown over the straw from these plants. Were evaluated the following parameters: frequency, abundance and density of spontaneous plants, importance value index (IVI); dry matter content (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), mineral matter (MM), insoluble protein in neutral detergent (IPND), insoluble protein in acid detergent (IPAD) and yield of CP of the silage corn; corn dry matter yield in each agricultural season and of bean, total yield from the systems and straw yield, considering the residual dry matter in the systems. The cropping of corn with the cover plants favored the selection of broadleaf plants. The showy rattlebox reduced the density and abundance of spontaneous plants when consorted with corn. The species Commelina benghalensis L. and Leonorus sibiricus L., showed the highest IVI for the corn/guandu bean/corn monoculture and corn/showy rattlebox/corn monoculture. The production of corn and corn silage whole plant in different crop rotation systems containing the green manure resulted in increases in dry matter, mineral matter and CP productivity. Highlighting the modality corn + jack bean/corn monoculture. The levels of ADF, NDF, IPDA and IPND were lower in the fall/winter season, showing the positive influence on the reduction N deposition in the less digestible fraction for in the whole plant silage grown on the straw of different green manures. The cultivation of intercropped corn and harvested with green spring/summer allows the production of whole plant silage whit adequate nutritional levels. The crop rotation systems that included the cover crops showed higher yield overall. The consortium with jack bean favored the corn yield in the first crop and the showy rattlebox straw the yield in the second crop. The systems corn + guandu beas/corn monoculture/oats/bean and corn/showy rattlebox/corn monoculture/forage radish/bean favored the bean yield. The corn monoculture/corn monoculture/fallow mode did not prioritize the accumulation of straw on the soil.